ANALISIS PROGRAM LITERASI SEKOLAH UNTUK PENINGKATAN KEMAMPUAN MEMBACA PESERTA DIDIK KELAS III SD INPRES DAGIMON, DISTRIK OBAA, KABUPATEN MAPPI - bapaimu (FKIP Universitas Cenderawasih, 2025)
Abstract: The School Literacy Program is a strategic response to persistent reading challenges in primary schools, especially in remote areas where learning resources and literacy exposure remain limited. This study analyzes the implementation, supporting and inhibiting factors, and impact of the School Literacy Program on the reading ability and reading interest of Grade III students at SD Inpres Dagimon, Obaa District, Mappi Regency, South Papua. The study employed a descriptive qualitative design involving the principal, Grade III teacher, parents, and 15 students selected purposively because of their direct involvement in the program. Data were collected through participatory observation, semi-structured interviews, and documentation, and were analyzed using reduction, display, and conclusion drawing supported by source and technique triangulation. The findings show that literacy activities were implemented through 15-minute pre-class reading, reading tutorials three times a week, and integrated classroom guidance. The program improved students' fluency, confidence, and home reading habits, although it remained at the habituation stage. Strengthening locally relevant reading materials, continuous evaluation, and school-family collaboration are required for sustainable literacy development. Keywords: school literacy program; reading ability; reading interest; elementary school; South Papua. Abstrak: Program Literasi Sekolah merupakan respons strategis terhadap persoalan rendahnya kemampuan membaca peserta didik sekolah dasar, terutama di wilayah terpencil yang menghadapi keterbatasan sumber belajar dan paparan literasi. Penelitian ini bertujuan menganalisis pelaksanaan, faktor pendukung dan penghambat, serta dampak Program Literasi Sekolah terhadap kemampuan dan minat membaca peserta didik kelas III SD Inpres Dagimon, Distrik Obaa, Kabupaten Mappi, Papua Selatan. Penelitian menggunakan desain kualitatif deskriptif dengan subjek kepala sekolah, guru kelas III, orang tua, dan 15 peserta didik yang dipilih secara purposif karena terlibat langsung dalam program. Data dikumpulkan melalui observasi partisipatif, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan dengan dukungan triangulasi sumber dan teknik. Hasil menunjukkan bahwa kegiatan literasi dilaksanakan melalui membaca 15 menit sebelum pembelajaran, les membaca tiga kali seminggu, dan bimbingan membaca terintegrasi. Program berdampak pada peningkatan kelancaran, keberanian, dan kebiasaan membaca di rumah, meskipun masih berada pada tahap pembiasaan. Penguatan bahan bacaan kontekstual, evaluasi berkelanjutan, dan kolaborasi sekolah-keluarga diperlukan agar program lebih berkelanjutan. Kata kunci: program literasi sekolah; kemampuan membaca; minat membaca; sekolah dasar; Papua Selatan